Review of e-Commerce Security Challenges (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
e-Commerce means nothing but the exchange of goods and services over the Internet.This paper gives a way for e-commerce security so as to improve confidence in customer. Web security has become most important issue now a day. Online payment system now a day most of time people uses online payment system for payment, so all the manual payment is replaced by online payment system. The main objective of this paper is to know the views of consumers towards the security aspects of e-commerce technology.  This paper gives the idea about the perception and awareness of security from the consumers’ views. The paper also examines the measures that can be taken so that the views of users can be changed to adopt this new on-line system. This new security challenges are the results of the use of the new technology and communication medium, and the flow of information from organization to organization, from organization to consumers, and also within the organization.